Psychological, biochemical and physiological responses of Brazilian soccer players during a training program - Silva, A. S. R. [UNESP]; Santhiago, V. [UNESP]; Papoti, M. [UNESP]; Gobatto, C. A. [UNESP] (Elsevier France-editions Scientifiques Medicales Elsevier, 2008)
Aims of the study. - The aim of this study is to investigate the behavior of the physiological, biochemical and psychological parameters in Brazilian soccer players during a training program.Materials. - Fifteen athletes were evaluated at the beginning (T1), in the middle (T2) and at the end (T3) of the training program. on the first day, at 7:30 am, before the blood collecting at rest for the determination of serum creatine kinase (CK), serum creatinine and serum urea, the athletes had their psychological parameters assessed by the profile of mood state questionnaire (POMS). After 90 min, they performed a 250-m sprint. on the second day at 8:30 am, the athletes had their alactic anaerobic performance measured and, after 40 min, they completed the aerobic test. Friedman test was used to verify the behavior of overtraining markers.Results. - There was a decrease in vigor score in T3 (p=0.01) compared with T1 and T2. In T3 (p=0.01), the athletes also showed an increase in serum creatinine levels compared to T1. Furthermore, in the same period, we verified a diminishing in the team performance.Conclusion. - The training program developed between T2 and T3 led to the fall of the vigor score, the increase in serum creatinine concentrations and the diminishing in team performance. (c) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: POMS; creatine kinase; creatinine; urea; team performance